Production of customized applications through a software development center - Pava Carmona, Luis Alberto
This article is the result of a project whose objective was to implement a Software Development Center for the Logistics and Ecotourism Promotion Center of Magdalena, in which the needs for information management and attention to citizens of the Center were initially analyzed and quantified. Training, to subsequently disclose to managers the need to systematize some missionary processes and plan the pilot methodology for the Software Development Center (CDS). It should be noted that the Magdalena Logistics and Ecotourism Promotion Center contributes to guaranteeing the training for work of those Colombians residing in the Caribbean region, supporting the fulfillment of the role that corresponds to the State to invest in social and technical development. Colombian workers, offering and executing comprehensive professional training, for the incorporation and development of people in productive activities that contribute to the social, economic and technological development of the country. Around the provision of services derived from the Integral and Administrative Professional Training, SENA has made innumerable efforts for information management and its publication or knowledge management for decision-making at hierarchical levels, a successful example is the implementation of an Optimized System for Active Integral Training - SOFIA Plus; It is no surprise that their contribution has guaranteed a better treatment of information, but some training centers have different demands regarding the use of administrative computing tools to automate and increase the use of the current technological architecture. Observing this need in the training center, the creation of a Software Development Center - CDS was planned, with which the apprentices of the technology program in Analysis and Development of Information Systems contribute significantly to the design, development, implementation and support of custom administrative tools.